2013
DOI: 10.1257/pol.5.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Let Them Have Choice: Gains from Shifting Away from Employer-Sponsored Health Insurance and Toward an Individual Exchange

Abstract: Most nonelderly Americans purchase health insurance through their employers, which sponsor a limited number of plans. Using a panel dataset representing over ten million insured lives, we estimate employees' preferences for different health plans and use the estimates to predict their choices if more plans were made available to them on the same terms, i.e., with equivalent subsidies and at large-group prices. Using conservative assumptions, we estimate a median welfare gain of 13 percent of premiums. A proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…14 Insurance coverage is usually generous, and consumers will face only a small fraction of a branded statin's $3/day price tag. Consumers in employer-sponsored insurance tend to have a limited number of choices (Dafny, Ho and Varela 2013) and are unlikely to select into insurance plans based on their coverage or cost sharing for particular drugs.…”
Section: Demandmentioning
confidence: 99%
“…14 Insurance coverage is usually generous, and consumers will face only a small fraction of a branded statin's $3/day price tag. Consumers in employer-sponsored insurance tend to have a limited number of choices (Dafny, Ho and Varela 2013) and are unlikely to select into insurance plans based on their coverage or cost sharing for particular drugs.…”
Section: Demandmentioning
confidence: 99%
“…Given those preference estimates, we then use choices in the pre-reform period to estimate the process driving the consideration set formation. Within the health care literature, Ho (2006) and Dafny, Ho and Varela (2013) also analyze the effect of removing choice constraints. However, in their settings the constrained choice sets are observed in the data and the papers evaluate the welfare effect of their removal in a counterfactual.…”
mentioning
confidence: 99%
“…Several studies have found that employees are generally sensitive to premium prices, a sensitivity that declines as employees age or experience longer job tenure or more health issues (Atherly, Curtis, and Thorpe 2005;Beaulieu 2002;Royalty and Solomon 1999;Strombom, Buchmueller, and Feldstein 2002;Wedig and Tai-Seale 2002)-behavior that could be explained as a desire to stick with a given insurer's provider network, or as an inertia effect. Overall, these results could mean that smaller choice sets yield more market-oriented behavior, findings that are contradicted by Dafny, Ho, and Varela (2010), who note several studies showing that price sensitivity declines in other large employer samples.…”
Section: Individual Insurance Markets Abroadmentioning
confidence: 76%